2020
DOI: 10.1007/s10347-020-00605-w
|View full text |Cite
|
Sign up to set email alerts
|

Microbial-, fusulinid limestones with large gastropods and calcareous algae: an unusual facies from the Early Permian Khao Khad Formation of Central Thailand

Abstract: The Early Permian (Kungurian) Khao Khad Formation of Central Thailand consists mostly of carbonates deposited on the western margin of the Indochina Terrane. This formation has yielded unusual microbial-fusulinid limestones with large gastropods which contribute most to the rock volume. With a height of more than 6 cm, the gastropods are amongst the largest Early Permian gastropods ever reported. Gastropods as major rock formers are rare in the Palaeozoic. This, and other recently reported invertebrate faunas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…Payne [177] proposed that gastropod size might be increased by local ecological factors, of which the most important is nutrient availability. Recently, Ketwetsuriya et al [178] concluded that high primary productivity was responsible for the presence of large gastropods (20-60 mm high) in the lower Permian of Thailand. At Lime Peak, large gastropods are found in MCF 2 beds that are very rich in green algae, foraminifera and organic content.…”
Section: Organisms' Distribution Within the Lime Peak Carbonate Systemmentioning
confidence: 99%
“…Payne [177] proposed that gastropod size might be increased by local ecological factors, of which the most important is nutrient availability. Recently, Ketwetsuriya et al [178] concluded that high primary productivity was responsible for the presence of large gastropods (20-60 mm high) in the lower Permian of Thailand. At Lime Peak, large gastropods are found in MCF 2 beds that are very rich in green algae, foraminifera and organic content.…”
Section: Organisms' Distribution Within the Lime Peak Carbonate Systemmentioning
confidence: 99%